دراسة أولية لمعالجة المخلفات السائلة لمعاصر الزيتون (ماء الجفت) باستخدام بعض الأحياء الدقيقة - كبيبو عيسى; عليا تميم (Latakia University Journal -Biological Sciences Series, 2019)
هدف هذا البحث إلى عزل سلالات من الأحياء الدقيقة المحلية القادرة على تفكيك المركبات الفينولية الموجودة في ماء الجفت. تم عزل الأحياء الدقيقة اللاهوائية من كل من ماء الجفت والتربة المشبعة بماء الجفت. اختبرت قدرة الأحياء الدقيقة المعزولة على تفكيك المركبات الفينولية، وذلك من خلال زرعها في أوساط زرعية تحتوي مركبات فينولية توجد بشكل شائع في ماء الجفت. حضرت أوساط زرع جرثومية تحتوي على 300mg/l من حمض الكافيك وحمض البروتوكاتيويك كل بمفرده وعند قيمتين لـpH 5.5 و7.0، وتمت عملية الحضن لمدة 24 ساعة عند درجتي حرارة 25°C و35°C. أظهرت النتائج أن الأحياء الدقيقة المعزولة قادرة على خفض المركبات الفينولية من التركيز الابتدائي 300mg/l إلى تراكيز منخفضة. تم اختيار أربع عزلات تميزت بقدرتها الكبيرة على تفكيك المركبات الفينولية وتم اختبار قدرتها على تفكيك كل من المركبات الفينولية الثمانية المدروسة بشكل منفرد(Caffeic acid, Protocatechuic acid, Feruulic acid, Vanilic acid, Cinnamic acid, Syringic acid, Syring aldehyde, Gallic acid) في أوساط مائية. تم تحديد كمية المركبات الفينولية المتبقية في أوساط الزرع بعد يوم وبعد ثلاثة وخمسة أيام من بدء الحضن. أظهرت النتائج أنه يمكن للأحياء الدقيقة المعزولة أن تخفض المركبات الفينولية بعد خمسة أيام من الحضن بنسبة تتراوح بين 60-93% وهذه النسبة تختلف تبعاً لنوع العزلة ونوع المركب الفينولي. This study aims to isolate local strain of microorganisms that can degrade the phenolic compounds existent in the olive mills waste water (OMWW). The anaerobic microorganisms are isolated from (OMWW) and from soil saturated with (OMWW). The isolated microorganism are assayed for its ability to degrade the phenol compounds by incubation in cultures. Each one contains one of the main two phenolic compounds (Caffeic acid and Protocatechuic acid) commonly found in (OMWW). The pH of culture is 5.5 (pH of OMWW) and 7.0, and the incubation is carried out at 25°C and 35°C. The results indicate that in 24 hrs of incubation the microorganisms are able to reduce the phenol concentration from 300 mg/l to low limits. Four strains of higher ability to degrade the phenolic compounds are selected to assay its ability to degrade eight phenolic componds (Caffeic acid, Protocatechuic acid, Feruulic acid, Vanilic acid, Cinnamic acid, Syringic acid, Syring aldehyde, Gallic acid) in liquid medium with the phenolic compounds as single substrates. The residual phenolic compounds in the culture are determined after 1, 3 and 5 days of incubation. The results indicate that in 5 days of incubation the isolated microorganisms are able to degrade 60-93% of phenolic compounds according to the microorganisms strains and phenol compounds respectively.